The Influence of Internal Communication on Job Performance: Controlling for Key Worker Characteristics - Ocra, Ben (Advances in Social Sciences Research Journal, 2021)
This study assessed the influence of internal communication on job performance, with relevant lurking variables controlled for as a new way of contributing to academic debate. This study was a correlational design that drew data from employees of University of Education Winneba (UEW). All 274 employees who met some selection criteria participated in this study. A self-reported questionnaire was used to gather data. Descriptive statistics, Pearson’s correlation test, ordinary least squares (OLS) regression analysis, and confirmatory factor analysis (CFA) were used to present findings of the study. The study found that downward, upward, and lateral communication in the university made a positive effect on job performance after controlling for job tenure, education, income, and employee level. Downward communication makes the strongest effect on job performance. It is therefore concluded that increasing the level of effectiveness in terms of downward, upward, and lateral communication in the university can increase the level of job performance.